2019
DOI: 10.1109/access.2019.2920239
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Distributed Honeypot Based on Blockchain

Abstract: Honeypot technology can be applied to efficiently attract attackers and exhaust their resources. However, the traditional static honeypot is easy to be recognized by anti-honeypot technology. By contrast, most of the dynamic honeypots can simulate the real system in time, thus interacting with an intruder in disguise. In this paper, we employ the dynamic property of honeypot in four kinds of services of our system. However, this dynamic property shows up in a location and identification, indicating that genuin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 35 publications
(34 reference statements)
0
23
0
Order By: Relevance
“…Based on our literature review, we found that there are not too many studies in this field; however, there are some rather promising achievements. 4,[16][17][18][19][20]…”
Section: • Firewallmentioning
confidence: 99%
“…Based on our literature review, we found that there are not too many studies in this field; however, there are some rather promising achievements. 4,[16][17][18][19][20]…”
Section: • Firewallmentioning
confidence: 99%
“…HoneyDOC consists of collaborative modules such as decoy, captor, and orchestrator. Shi et al [6] proposed a blockchain-based Honeypot, which uses a dynamic mechanism of combining the functionalities of Low and High interaction Honeypot. Their work consists of a real system in time architecture that is widely used to capture real-time attacks.…”
Section: A Honeypotmentioning
confidence: 99%
“…To reduce the false alarm rate of the detection system, Meng et al [37] designed a hierarchical framework to mine high-threat alerts from a large number of alarm logs, to provide available information for the management system to modify the judgment policy. In [38], the authors developed a dynamic distributed honeypot and combined it with the Blockchain platform, to discover attacks and resist anti-honeypot technology in time. This scheme achieved high reliability, high security, and low response time.…”
Section: Security Monitoring and Surveillance Technologymentioning
confidence: 99%